The devil's best trick : how the face of evil disappeared - Sullivan, Randall (Atlantic Monthly Press, 2024)
"A sweeping and comprehensive search for the origins of belief in a Satanic figure across the centuries, The Devil's Best Trick is a keen investigation into the inescapable reality of evil and the myriad ways we attempt to understand it. Instructive, riveting, and unnerving, this is a profound rumination on crime, violence, and the darkness in all of us. In The Devil's Best Trick, Randall Sullivan travels to Catemaco, Mexico, to participate in the "Hour of the Witches"-an annual ceremony in which hundreds of people congregate in the jungle south of Vera Cruz to negotiate terms with El Diablo. He takes us through the most famous and best-documented exorcism in American history, which lasted four months. And, woven throughout, he delivers original reporting on the shocking story of a small town in Texas that, one summer in 1988, unraveled into paranoia and panic after a seventeen-year-old boy was found hanging from the branch of a horse apple tree and rumors about Satanic worship and cults spread throughout the wider community. Sullivan also brilliantly melds historical, religious, and cultural conceptions of evil: from the Book of Job to the New Testament to the witch hunts in Europe in the fifteenth through seventeenth centuries to the history of the devil-worshipping "Black Mass" ceremony and its depictions in nineteenth century French literature. He brings us through to the "Satanic Panic" of the 1980s and the story of one brutal serial killer, pondering the psychology of evil. He weaves in writings by John Milton, William Blake, Oscar Wilde, Edgar Allan Poe, Nathaniel Hawthorne, Herman Melville, Mark Twain, and many more, among them Charles Baudelaire, from whose work Sullivan took the title of the book. Nimble and expertly researched, The Devil's Best Trick brilliantly melds cultural and historical commentary and a suspenseful true-crime narrative."--